Respostas

2014-06-15T21:16:22-03:00
X² - 15 = 2x
x² - 2x - 15 = 0

a=1       b=-2      c=-15



Δ=b²-4.a.c
Δ=(-2)²-4.1.(-15)
Δ=4+60
Δ=64   ⇒  raiz de 64 é 8



x'=-(-2) + 8    +2+8      +16
    ¨¨¨¨¨¨¨¨¨¨¨¨ =¨¨¨¨¨¨¨¨¨= ¨¨¨¨¨¨¨¨¨=  8
      2.1            2            2  
 
 

x"=-(-2) - 8      2 - 8     -6
    ¨¨¨¨¨¨¨¨¨¨¨¨ = ¨¨¨¨¨¨¨¨ = ¨¨¨¨¨  = -3              S; (8, -3)
        2.1           2         2
2 5 2
2014-06-15T21:17:18-03:00
X² - 15 = 2x
x² - 2x - 15 = 0

delta = b² - 4ac
delta = 4 + 60
delta = 64

x = - b + - raiz de delta / 2a
x = 2 + - 8 / 2
x' = 5
x'' = - 3

S = {5, -3}
2 5 2